Experimental Studies Indicate That ST-2223, the Antagonist of Histamine H3 and Dopamine D2/D3 Receptors, Restores Social Deficits and Neurotransmission Dysregulation in Mouse Model of Autism - Nermin Eissa; Karthikkumar Venkatachalam; Petrilla Jayaprakash; Priya Yuvaraju; Markus Falkenstein; Holger Stark; Bassem Sadek (Pharmaceuticals, 2022)
Altered regulation of neurotransmitters may lead to many pathophysiological changes in brain disorders including autism spectrum disorder (ASD). Given the fact that there are no FDA-approved effective treatments for the social deficits in ASD, the present study determined the effects of chronic systemic treatment of the novel multiple-active H3R/D2R/D3R receptor antagonist ST-2223 on ASD-related social deficits in a male Black and Tan Brachyury (BTBR) mice. ST-2223 (2.5, 5, and 10 mg/kg, i.p.) significantly and dose-dependently mitigated social deficits and disturbed anxiety levels of BTBR mice (p < 0.05) in comparison to the effects of aripiprazole (1 mg/kg, i.p.). Moreover, levels of monoaminergic neurotransmitters quantified by LC-MS/MS in four brain regions including the prefrontal cortex, cerebellum, striatum, and hippocampus unveiled significant elevation of histamine (HA) in the cerebellum and striatum; dopamine (DA) in the prefrontal cortex and striatum; as well as acetylcholine (ACh) in the prefrontal cortex, striatum, and hippocampus following ST-2223 (5 mg/kg) administration (all p < 0.05). These in vivo findings demonstrate the mitigating effects of a multiple-active H3R/D2R/D3R antagonist on social deficits of assessed BTBR mice, signifying its pharmacological potential to rescue core ASD-related behaviors and altered monoaminergic neurotransmitters. Further studies on neurochemical alterations in ASD are crucial to elucidate the early neurodevelopmental variations behind the core symptoms and heterogeneity of ASD, leading to new approaches for the future therapeutic management of ASD.